Kurangnya Literasi Keuangan yang Berdampak pada Kecurangan dalam Pekerjaan Khususnya di Perusahaan Retail - Prasetyo, Ardi (Economie: Jurnal Ilmu Ekonomi, 2025)
In this era where everything is easily accessible, there are many benefits provided by technological developments, from the smallest things such as the ease of obtaining information to the biggest things such as the ease of connecting with people in any part of the world. But with the ease of this information, there are still many people who have minimal knowledge about financial management, this will have a fatal impact, not only on themselves, but can also have an impact on their environment. As a result of this lack of knowledge, many people are currently having difficulty distinguishing between needs and wants, which is exploited by irresponsible people who offer the promise of quick profits through online gambling and trapping online gambling victims into taking out online loans.